STRATEGI PENGEMBANGAN PENGOLAHAN KOPI ARABIKA SEBAGAI DAYA TARIK WISATA GASTRONOMI DI DESA CATUR, KINTAMANI, BALI - I Made Hendrayana (JURNAL KEPARIWISATAAN, 2022)
Catur Village is a center for Kintamani Arabica Coffee production, the distribution of the coffee products has been carried out throughout Bali to foreign countries such as Japan, Europe, America, and Australia with the brand "Kopi Catur Arabika Kintamani". As a tourist village, Catur needs to have a strong tourist attraction to attract tourist visits. The study of the development of the Kintamani Arabica Catur Coffee processing attraction as a gastronomic tourist attraction is the right step to create a strong story or story in the minds of tourists. The purpose of this study was to determine the development strategy of coffee processing as a gastronomic tourist attraction. The research method used is qualitative using SWOT analysis. The results show that there are 13 strategy formulations that can be used in the development of coffee processing as a gastronomic tourist attraction, of these 13 strategies there are 11 strategies that have been realized, but the realization must be further optimized.